"My first 48 hours out": drug users' perspectives on challenges and strategies upon release from prison - Daniela Jamin; Wouter Vanderplasschen; Orphée Sys; Marie Jauffret-Roustide; Laurent Michel; Philippe Trouiller; Andreia Neisa; Mariana Homen; Vânia Mendes; Heino Stöver (BMC, 2021)
Abstract Background Prisoners report much higher prevalence rates of drug use and more harmful consumption patterns than the general population. People who use drugs have above-average experiences with the criminal justice system in general, and the prison system and subsequent release situations in particular. Release from prison is associated with increased mortality rates among drug users due to the risk of overdose. The EU-funded project 'My first 48 hours out' aimed to address the gaps in continuity of care for long-term drug users in prison and upon release, with a special focus on drug user's perspectives on needs and challenges upon release. Methods A multi-country (Belgium, France, Germany and Portugal) qualitative study was set up to explore drug users' perceptions of drug use and risk behaviour upon prison release, experiences of incarceration and release, and strategies to avoid risks when being released. In total, 104 prisoners and recently released persons with a history of drug use participated in semi-structured interviews and focus groups discussions on these topics. Results Respondents pointed out that there are numerous challenges for people who use drugs when released from prison. Lack of stable housing and employment support were frequently mentioned, as well as complex administrative procedures regarding access to services, health insurance and welfare benefits. Besides structural challenges, individual issues may challenge social reintegration like 'old habits', mental health problems and disrupted social networks. As a result, (ex-)prisoners adopt individual strategies to cope with the risks and challenges at release. Conclusion Measures to prepare prisoners for release often do not focus on the individual and specific challenges of persons who use drugs. Psychosocial and medical support need to be improved and adjusted to drug users' needs inside and outside prison. To improve the quality and continuity of care around release, the perspectives and coping strategies of people who use drugs should be used to better address their needs and barriers to treatment.